(untitled) (Research in Agriculture Livestock and Fisheries, 2017)
Carps are the main species for the aquaculture system in Bangladesh, and the production of these species completely depends on timely and adequate supply of quality seeds. In hatcheries, since middle of nineties, stock deterioration was reported because of poor brood stock management and inbreeding depression and still though both public and private hatcheries and nurseries are producing fish seeds, but there has been a growing concern over the availability of good quality seeds for sustainable fish production. For that reason, the production of quality carp spawns and fingerlings are essential for desired production of fish in Bangladesh. We reviewed the present status of carp hatcheries along with ongoing practices of breeding in different carp hatcheries for sustainable production strategies in this region. Res. Agric., Livest. Fish.4(2): 123-129, August 2017